“My lot is cast in with my sex and country”: Generic Conventions, Gender Anxieties and American Identity in Emma Hart Willard’s and Catherine Maria Sedgwick’s Travel Letters - Małgorzata Rutkowska (Anglica. An International Journal of English Studies)
The article analyses generic conventions, gender constraints and authorial self-definition in two ante-bellum American travel accounts – Emma Hart Willard’s Journal and Letters, from France and Great Britain (1833) and Catharine Maria Sedgwick’s Letters from Abroad to Kindred at Home (1841). Emma Hart Willard, a pioneer in women’s higher education and Catharine Maria Sedgwick, an author of sentimental novels, were influential figures of the Early Republic, active in the literary public sphere. Narrative personas adopted in their travel letters have been shaped by the authors’ national identity on the one hand and by ideals of republican motherhood, which they propagated, on the other. Both travelogues are preceded with apologies filled with self-deprecating rhetoric, typical for women’s travel writing in the early 19th century and both are intended to instruct the American reader. Other conventional features of American antebellum travel writing include comparisons between British and American government and society with a view of extolling the latter as well as avid interest in social status and public activities of European women. Willard and Sedgwick deal with possible gender anxieties of their upper middle-class female readers by assuring them that following one’s literary or educational vocation in the public sphere does necessarily mean compromising ideals of true womanhood in private life.